RELATIONSHIP BETWEEN ATTACHMENT AND ADJUSTMENT WITH CHRONIC PAIN; WITH STUDY THE MODERATOR ROLE OF RESILIENCY - SakinehJulaieha; Dehkordi, MahnazAliakbari; Shagaghi, Farhad; Lak, Afsaneh; Marziehkakanejadifard (International Journal of Research -GRANTHAALAYAH, 2016)
The present study investigated the relationship between attachment style with adjustment and resiliency in chronic pain patients and probable mediating role of resiliency between attachment and adjustment. Adult Attachment Inventory; Depression‚ Anxiety‚ Stress Scale (DASS_21) Resiliency Scale (CS_RISC) and Roland–Morris Disability Questionnaire (RDQ). Data were analyzed using parson’s correlation and regression. Results revealed that avoidant and ambivalent attachment styles negatively correlated with adjustment (positively correlated with depression, anxiety and stress) and positively with resiliency. Secure attachment wasn’t correlated with none of them. Resiliency didn’t mediate the impact of attachment style on adjustment. These findings suggest that insecure attachment style is a vulnerability factor for adjustment with chronic pain and predicts lower resiliency in these patients. Briefly present the conclusions and importance of the results. Concisely summarize the study’s implications. Please do not include any citations in the abstract.